Radiosensitization in Pediatric High-Grade Glioma: Targets, Resistance and Developments - Metselaar, Dennis S.; du Chatinier, Aimée; Stuiver, Iris; Kaspers, Gertjan J. L.; Hulleman, Esther (Frontiers in Oncology, 2021)
Pediatric high-grade gliomas (pHGG) are the leading cause of cancer-related death in children. These epigenetically dysregulated tumors often harbor mutations in genes encoding histone 3, which contributes to a stem cell-like, therapy-resistant phenotype. Furthermore, pHGG are characterized by a diffuse growth pattern, which, together with their delicate location, makes complete surgical resection often impossible. Radiation therapy (RT) is part of the standard therapy against pHGG and generally the only modality, apart from surgery, to provide symptom relief and a delay in tumor progression. However, as a single treatment modality, RT still offers no chance for a cure. As with most therapeutic approaches, irradiated cancer cells often acquire resistance mechanisms that permit survival or stimulate regrowth after treatment, thereby limiting the efficacy of RT. Various preclinical studies have investigated radiosensitizers in pHGG models, without leading to an improved clinical outcome for these patients. However, our recently improved molecular understanding of pHGG generates new opportunities to (re-)evaluate radiosensitizers in these malignancies. Furthermore, the use of radio-enhancing agents has several benefits in pHGG compared to other cancers, which will be discussed here. This review provides an overview and a critical evaluation of the radiosensitization strategies that have been studied to date in pHGG, thereby providing a framework for improving radiosensitivity of these rapidly fatal brain tumors.